Transgenerational trauma: Diagnosis of phenomena of family scenarios using the reavisia method in the structure of psychological and psychosomatic pathology - Katiukhin Олег (Psychosomatic Medicine and General Practice, 2025)
The work shows the investigative role of the inheritance and mechanisms of family scenarios in the development of psychological problems (A. Schutzenberger, 1998, C. Steiner, 2007), psychiatric illness and psychosomatic pathology for additional help from the ceranovan trance camps “in reality” to the reavisia method (Katostrovskii, 2023). Due to the current development of psychotherapy, the method shows the possibility of objectively explaining the mechanisms of transgenerational (“through generations”) transmission of traumatic experiences and the formation of family scenarios in the structure various psychological problems and psychosomatic pathologies. The method can eliminate the widespread use in psychotherapeutic interventions of psychosomatic medicine.